Sign Control of Magnetoresistance Through Chemically Engineered Interfaces. (22nd October 2014) - Ciudad, David; Gobbi, Marco; Kinane, Christy J.; Eich, Marius; Moodera, Jagadeesh S.; Hueso, Luis E.
<x xml:space="preserve">Abstract</x> Chemically engineered interfaces are shown to produce inversions of the magnetoresistance in spintronic devices including lithium fluoride interlayers. This behavior is explained by the formation of anti‐ferromagnetic difluoride layers. By changing the order of deposition of the different materials, the sign of the magnetoresistance can be deterministically controlled both in organic spin valves and in inorganic magnetic tunnel junctions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>